Analysis of the Read‑Aloud Strategy on the Reading Interest of Grade V Students at SDN 4 Kore - Fitria, Fitria; Komalasari, Desy Ningsih; Syarifuddin, Syarifuddin (Journal of Educational Sciences, 2025)
Reading aloud is a very important skill for elementary school students. This study aims to (1) analyze the reading-aloud strategy implemented by teachers in the school and (2) determine the impact of implementing the reading-aloud strategy on students’ reading interest. The research was conducted at SDN 4 Kore in Grade 5, with a total of 14 students. This study used a descriptive qualitative approach, with data collection techniques including classroom observation, interviews with teachers and students, and questionnaires distributed to all 14 students as respondents. The observation results showed that the teacher consistently applied the read-aloud strategy in Indonesian language instruction in an engaging way—using varied intonation, facial expressions, and involving students in discussions after reading. The interviews confirmed that students felt happier learning when the teacher read aloud, as it helped them understand the story content more easily. Additionally, the questionnaire data revealed that most students experienced an increase in reading interest, ranging from a desire to read books independently to increased visits to the library. In conclusion, the read-aloud strategy was proven to foster students’ reading interest by creating an enjoyable and meaningful reading experience.